Diel vertical migration rates of the dinoflagellate species Margalefidinium polykrikoides in a lower Chesapeake Bay tributary - Clayton, Sophie; Chrabot, Jacqueline B.; Echevarria, Michael; Gibala-Smith, Leah; Mogatas, Kathryn; Bernhardt, Peter; Mulholland, Margaret R. (Frontiers in Microbiology, 2024)
Margalefidinium polykrikoides is a mixotrophic dinoflagellate harmful algal bloom (HAB) species that blooms annually in the lower Chesapeake Bay. M. polykrikoides undertakes a diel vertical migration (DVM) which may give it a competitive advantage over purely phototrophic organisms who cannot access deeper nutrient pools and allow it to form large toxic blooms. Laboratory-based estimates of M. polykrikoides' DVM rates suggest that it is one of the fastest known dinoflagellate swimmers and understanding this behaviour is likely important for modeling and predicting M. polykrikoides blooms. However, to date, no field-derived estimates of M. polykrikoides’ DVM rates have been made in the Chesapeake Bay. In this study, we conducted four targeted field experiments to investigate the DVM of M. polykrikoides in the Lafayette River, a sub-tributary of the Chesapeake Bay. Vertical profiles of chlorophyll a fluorescence collected at least every 2 hours over diel periods were used to track the DVM of M. polykrikoides during blooms. The maximum observed DVM rate for M. polykrikoides was 2.5 m hr-1, with mean DVM rates around 1.3 m hr-1 for both ascents and descents. As in studies from other regions, our results show that M. polykrikoides’ ascent to/descent from the surface initiates before sunrise/sunset, suggesting phototaxis is not the primary trigger of their DVM. However, unlike in other studies where M. polykrikoides was observed to modulate its DVM to avoid excessively warm temperatures (≥ 30°C), we do not observe active thermotaxic avoidance, despite ambient temperatures exceeding their optimal threshold.